ANALYSIS OF THE EFFECT OF PROTEIN SNACKS ON THE NUTRITIONAL STATUS OF ELEMENTARY SCHOOL STUDENTS IN WEST ACEH IN THE GENIUS PROGRAM IN 2023 - Agustiarni; Itza Mulyani; Wardah Iskandar; Rinawati (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Student nutritional status is a crucial indicator of health and development, particularly regarding adequate nutrition. One effective intervention to enhance nutritional status is providing high-protein snacks. Indonesia's Genius Program aims to improve child nutrition through targeted interventions in select schools nationwide, including 17 schools in Aceh. Quantitative study analyzed the impact of high-protein snacks on student nutritional status in West Aceh elementary schools using secondary data from the 2023 Genius Program. Employing a quantitative design and Wilcoxon statistical analysis, 339 students were categorized into three nutritional status groups based on BMI-for-age z-scores: undernutrition, good nutrition, and overnutrition. Results showed that 14-day high-protein snack provision significantly improved student nutritional status, increasing good nutrition proportions and reducing undernutrition cases. The Genius Program in West Aceh elementary schools (2023) effectively enhanced student nutritional status by reducing undernutrition and increasing good nutrition proportions. Recommendations include extending program duration and expanding sample sizes for future research generalization.